Accurate and sensitive determination of selected hormones, endocrine disruptors, and pesticides by gas chromatography–mass spectrometry after the multivariate optimization of switchable solvent liquid‐phase microextraction. Issue 14 (1st July 2018) - Chormey, Dotse Selali; Bodur, Süleyman; Baskın, Dilgeş; Fırat, Merve; Bakırdere, Sezgin
Abstract: Switchable solvent liquid‐phase microextraction was combined with gas chromatography and mass spectrometry to improve the sensitivity and accuracy for the determination of selected endocrine disruptors, pesticides, and hormones. The extraction method was used to complement gas chromatography with mass spectrometry by preconcentrating analytes for trace determinations. A Box–Behnken experimental design was used to evaluate the main variables and their interaction effects, and optimum parameters were selected based on the model of experimented results. Application of optimum extraction conditions to mixed standard solutions yielded limits of detection and quantitation values between 0.20–13 and 0.90–46 ng/mL, respectively. The accuracy and the applicability of the developed method was checked in tap water and two different wastewater samples by spiked recovery tests. The percent recoveries recorded for the analytes were between 91 and 110%, and percent relative standard deviation values were all below 10%. The results indicate that the method can be used for the accurate and sensitive determination of these analytes in the presented matrixes.